Banking without branches - Niklas Amberg; Bo Becker (Sveriges Riksbank, 2024)
The decline in cash use and growing use of digital distribution for retail banking leads to a reduced need for bank branches. Lending to small and medium sized firms (SMEs) has not benefited as much from a digital transformation, and widespread branch closures may reduce their supply of credit. Using the closing of two thirds of Swedish branches as a laboratory, we document that corporate lending declines rapidly following branch closures, mainly via reduced lending to small and young firms. The reduced credit supply has real effects: local firms experience a decline in employment and sales and an increase in exit risk after branch closures. Our results thus suggest that the disappearance of bank branches have far-reaching implications for the economy.
Keywords: D22; G21; G32; R12; R32; 330; Banks; branch closures; credit supply